The characterization of IgG antibodies to GalNAc beta-terminated glycans of gastric cancer survivors - Smorodin, E.P.; Sergeyev, B.L.; Kurtenkov, O.A. (Experimental Oncology, 2014)
The elevated anti-GalNAcβ IgG level of serum was shown to be associated with the significantly better survival of patients with gastrointestinal cancer. Aim: To characterize the specificity of IgG antibodies to GalNAcβ-terminated glycans of long-term gastric cancer survivors. Methods: Serum antibodies and affinity-isolated antibodies were analysed by the indirect and competitive ELISA using glycan-polyacrylamide (PAA) conjugates as well as by isoelectric focusing and Western blotting. Results: In the serum probes, a partial cross-reactivity of antibodies to GalNAcβ, GalNAcβ1–3Galβ (X2di), GalNAcβ1–3GalNAcβ (PFdi) and GlcNAcβ was observed. The isolated anti-GalNAcβ IgGs demonstrated the cross-reactivity to the X2di glycan mainly. The affinity of the X2di-PAA to anti-GalNAcβ IgGs was 11–21 times lower than that of the GalNAcβ-PAA. Anti-X2di and anti-PFdi IgGs demonstrated monoreactivity to their key glycans-PAA used in isolation. The IC50 values of key glycoconjugates ranged from 1 to 5 · 10⁻⁷ M. No polyreactivity of antibodies to the unrelated antigens (ferritin, casein and DNA) was found. The polyclonal or oligoclonal distribution of IgG bands was established and the monoreactivity of antibodies was not associated with the clonal distribution of bands. Conclusion: The cross-reactivity of anti-GalNAcβ antibodies to X2di and related glycans deserves attention in the clarification of the role of antibodies in cancer progression and enhancement of the prognostic potential in the combined determination of antibody markers. Key Words: gastric cancer, glycan-polyacrylamide, anti-GalNAc-beta, para-Forssman, X2, oligoclonal IgG, microbiota.